Development and single dose clinical pharmacokinetics investigation of novel zein assisted- alpha lipoic acid nanoencapsulation of vardenafil. Issue 1 (December 2018) - Ahmed, Osama
Abstract The aim of this study was to utilize the biocompatibility of the natural ingredients zein and alpha lipoic acid (ALA) as a novel nanosphere matrix formulation that encapsulates vardenafil (VRD) for improved drug delivery and bioavailability. Three formulations were prepared using zein: ALA ratio of 1:1, 2:1 and 3:1 by liquid–liquid phase separation method. Physicochemical characterization andin vitro diffusion evaluation were carried out for the prepared formulations. A single dose clinical pharmacokinetic study was carried out for the selected formulation. Results revealed VRD formulations showed particle size of 836.7 ± 191.3, 179.8 ± 18.4 and 147.3 ± 18.1 nm and encapsulation efficiency of 55.72 ± 4.36, 65.33 ± 7.82 and 69.38 ± 6.83% for F1, F2 and F3, respectively. Single dose clinical pharmacokinetic results, in healthy human volunteers, showed improved VRD bioavailability by 2.5 folds from nanosphere formula (F3) compared with the marketed tablets. The formulation of novel zein-ALA nanospheres offers the possibility for application of a biocompatible nano-carrier system in drug delivery for improved drug delivery and efficacy.